Awareness and Understanding of Decision-Making Capacity and Its Relationship to Legally Valid Consent for Older Patients in Dentistry. Issue 3 (September 2020) - Dhadwal, Amardeep Singh; Sibanda, Lwazi; Blum, Igor R.
With a growing ageing population and increased life expectancy in the UK, oral healthcare professionals will be exposed to a greater number of patients with health conditions which may affect cognitive function, communication and capacity to consent to treatment. This often gives rise to a conundrum which clinicians may face when considering capacity, consent and the legal implications and frameworks surrounding this. Assessing patient capacity is encountered routinely in dental practice and so oral healthcare professionals should be well informed of their responsibilities in this context. This article summarises and introduces readers to key concepts regarding consent and capacity with reference to relevant cross-jurisdictional legislation.